An Abnormally Abnormal Intangible: Stock Returns on Customer Satisfaction. (September 2016) - Fornell, Claes; Morgeson, Forrest V.; Hult, G. Tomas M.
Sorescu and Sorescu (2016) andBharadwaj and Mitra (2016) have made a number of insightful observations and suggestions for future research regarding stock returns on customer satisfaction. They have also provided a series of assessments of a study byFornell, Morgeson, and Hult (2016) that focus on abnormal returns on customer satisfaction. Building on the original study, as well as the two commentaries and previous research, the study's authors argue that the published empirical evidence is quite consistent in favor of abnormal returns on customer satisfaction. These findings are also supported by the new analysis of Sorescu and Sorescu, who make several important contributions, not only regarding the persistence of abnormal returns over and beyond the technology sector but also with respect to the critical importance of industry classification in the context of customer satisfaction—something that definitely calls for more research attention. In fact, there are many avenues for future research on the economic and financial impact of customer satisfaction, as laid out in the commentaries, the authors' original article, and this response.